The effect of financial leverage on corporate value: A study from the food and beverage industry in Vietnam - Nguyen, Huu Nghia (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
Financial leverage is one of the crucial corporate policies that indicate the proportion of debts to total firm assets. This paper investigates the effect of financial leverage on firm value in the Vietnam’s food and beverage industry. The study employs data of food and beverage public companies listed on the Vietnamese Stock Exchanges in the period 2014 – 2020. Numerous analysis methods are used including pool OLS, fixed effect and random effect models. The results of this paper reveal that financial leverage has a positive effect on corporate value in food and beverage industry in Vietnam. Firm size exerts a positive effect on firm value. The findings show that asset tangibility and firm profitability have significant and positive relationship with firm value. The research results are useful for planning financial leverage policies.